Use of antibiograms and changes in bacterial resistance patterns in the Ross Tilley Burn Centre - Josephine A. D'Abbondanza; Natalia Ziolkowski; Sarah Rehou; Shahriar Shahrokhi (Elsevier, 2024)
Background: Infection is a leading cause of death in burn patients and increasing antimicrobial resistance has made management difficult. Antibiograms are a useful tool to guide empiric treatment of infections, however, inappropriate prescribing may influence resistance. The objective of this study is to describe trends in antibiotic susceptibilities and use in a Canadian burn population pre- (PrA) and post-introduction (PoA) of antibiograms. Methods: We performed a retrospective review of patients admitted to an ABA-verified Burn Centre for two years pre- (2013-2014) and post-introduction (2016-2017) of institutional antibiograms receiving empiric broad-spectrum antibiotics (meropenem, piperacillin-tazobactam, and/or vancomycin). Results: A total of 864 patients were admitted during the study period with 257 patients PrA and 239 patients PoA included. Average age, % total body surface area (%TBSA), and length of stay were similar between cohorts. Administration of empiric meropenem increased (43.2 % vs. 56.8 %) and piperacillin-tazobactam decreased (60.6 % vs. 39.4 %), which was significant (p = 0.002). There was a significant decrease in the overall use of empiric antibiotics (p = 0.002) and sepsis (p = 0.008) since the inception of antibiograms. There was no significant difference in use of targeted antibiotics pre- or post-antibiogram introduction. Conclusions: Our study demonstrates that since the introduction of antibiograms, there has been a decrease in overall use of empiric antibiotics, a significant decrease in administration of piperacillin-tazobactam, and improvement in sepsis rates. However, these antibiotics were not routinely targeted to the appropriate organism and therefore may contribute to multi-drug resistant organisms in a burn population.